The demand ratio and effective agents in blood transfusion in patients undergoing prostate surgery - Kmyar Tavakkoli Tabasi; Shabnam Mohammadi; Hoda Jalayer (فصلنامه دانشگاه علوم پزشکی جهرم, 2012)
Introduction: Benign prostatic hyperplasia is a common disease in men for which surgery is a method of treatment. In some cases, due to bleeding transfusion is required during the surgery. In this study, the need for blood transfusion and its effective factors in the candidates of surgical intervention were investigated because of benign prostatic hyperplasia. Materials and Method: In this descriptive cross-sectional study, the ratio of transfusion and effective factors was analyzed in 700 referred patients undergoing prostatic surgery in Imam Reza hospital during 1386-1389. Results: Of total 700 patients, only 14 received blood (2%). As to the type of surgery, 64.3% in the transfused group, and 28.8% in the group without transfusion underwent suprapubic surgery the difference between them was significant statistically (p=0.01). 50% of the patients in the transfused group, and 86.4% in the group with no transfusion had HCT<35 this difference was also significant (p=0.002). Other factors such as age or basic disease were not significantly different in the two groups. Conclusion: Due to the low percentage of transfusion (2%), its relationship with the type of surgery, HCT, and the costs of blood storage and crossmatching, it is suggested that only for cases with HCT less than 35 and candidates of suprapubic surgery packed cells should be reserved. For other patients, other tests such as antibody screening can be used. This test is less expensive and easier than the previous tests in addition, in this type it is not necessary to prepare blood before surgery.